Optimizing Performance at Signalized Intersection through Signal Optimization: A Case Study at Padmodaya Chowk, Putalisadak - Amgain, Arbin; Silwal, Satkrit; Karmacharya, Nikshaya; Panthi, Prashant; Bohara, Dhiraj (International Journal on Engineering Technology and Infrastructure Development, 2025)
Putalisadak is one of the busiest places in Kathmandu which faces severe traffic congestion during peak hours leading to prolonged delays, increased air pollution and heightened accident risks. It is a crucial hub connecting major roads to important areas through the three-legged intersection of Padmodaya Chowk. Data such as traffic volume, pedestrian volume and saturation flow were collected through video-graphic survey over 3 days in the morning peak hours and the evening peak hours. Other parameters such as cruise speed, back of queue length and intersection geometry were collected through field surveying in the site. PCU values were calculated through Indo HCM values. Indo HCM is a highway capacity manual of India that provides guidelines and methods unique to the conditions and requirements of the road network. The traffic volume was found to be much higher in the morning peak hour from 9:30 to 10:30 am than the evening peak hour. So, the data of morning peak hour was inputted in SIDRA Intersection 8 software along with other parameters by creating a base model each for both the intersections. The calibration and validation of the data obtained from the SIDRA software was done to get accurate results and verify of the data The existing conditions of the intersections were found by determining the average delay, queue length and level of service of the intersections and found to be sec average delay, 159.4m queue length. The existing level of service of the Padmodaya Chowk was found to be “D” using the Indo HCM values. So, the traffic signals of the intersection was optimized which led to almost no improvement in the overall LOS of the intersections but significant reduction in the average delay and queue length in the approaches of the intersection.